Feed attractants in aquaculture - the chemical composition of aquacultured Ulva lacinulata (Chlorophyta) - Etwarysing, Lekraj (Department of Biological Sciences, 2025)
For more than two decades, cultivation of the green seaweed Ulva lacinulata (Ulvales) has proven to be commercially viable and an integral part of the South African abalone aquaculture industry. This seaweed is not sold, but mainly used as feed for the abalone Haliotis midae (Lepetellida) and on some farms for the bioremediation of abalone effluent water to enable partial recirculation in integrated abalone-Ulva systems. The Ulva grown in farm effluent has higher protein content than material found in nature and has been found to be a suitable supplementary feed for secondary high commercial value macroalgivores, including the local sea urchin Tripneustes gratilla (Camarodonta). Under laboratory conditions, T. gratilla has demonstrated hierarchical feeding preference to this aquacultured Ulva over other seaweed species. Inclusion of this alga in the diet of this urchin has been shown to act as a feed attractant as well as act as a feed stimulant, but the mechanisms for this remain unknown. The aim of this research was to identify the fractions or compounds from aquacultured Ulva responsible for the attractant activity of this seaweed towards the sea urchin T. gratilla as well as to evaluate their effectiveness and minimum effective concentrations. This research also assessed the effect of nutrient variation on the lipid and fatty acid composition of aquacultured Ulva and evaluated the volatile organic compounds produced by this seaweed. Crude Ulva extract, prepared from solvent extraction (dichloromethane - methanol), was fractionated to produce nine fractions (F1 → F9), with increasing polarity and solubility. The attractiveness and stimulatory effects of the Ulva fractions (extracts equivalent to 1 g fresh Ulva; FU) along with a control (no extract) were tested on T. gratilla in a chemosensory trial. The touch and grazing preferences of the urchin, placed in the center of a circular bioassay tank, were monitored over a period of 75 mins. A touch preference was assigned when the tube feet of T. gratilla touched the sample zone (Avicel® bioassay plate) containing an Ulva fraction, placed at the periphery of the tank, while a feed preference was allocated when the sample zone containing an extract was grazed. An urchin can show touch and grazing preference to one or multiple Ulva fractions in a bioassay. Bioassays were repeated using 120 individual sea urchins. Data collected showed clear evidence for the preferences of T. gratilla for the polar Ulva fractions F8 and F9. The predicted probability ranking for Ulva fractions to attract T. gratilla was F8 > F9 > F5 ≥ F6 > F4 > F7 > F3 > F2 ≥ F1, while the predicted probability ranking for Ulva fractions to stimulate T. gratilla to feed was F9 > F8 > F5 ≥ F6 > F4 ≥ F7 > F3 > F2 > F1. Glycerolipids, monogalactosyldiacylglycerol (MGDG) from F8 and a mixture of compounds including diacylglyceryl-N,N,N-trimethyl-homoserine (DGTS), digalactosyldiacylglycerol (DGDG), dialkylglycerophosphate (PA), lysophospholipid (LPG) and sulfoquinovosylmonoacylglycerol (SQMG) from F9, were identified as the most probable feed stimulants for T. gratilla. The minimum effective concentrations (MECs) of the stimulatory Ulva fractions F8 and F9 were subsequently evaluated on T. gratilla. In total, five different concentrations for both F8 and F9 equivalent to 0.05, 0.5, 1.0, 2.0 and 5.0 g fresh Ulva (FU) were tested on T. gratilla in chemosensory trials. The touch and grazing preferences of the urchins (n = 46 for each fraction) were recorded, and results showed that T. gratilla was able to perceive chemicals emitted by the treatment containing extracts equivalent to 0.05 g FU for both F8 and F9. However, the most effective treatments at attracting and stimulating T. gratilla to feed contained F8 equivalent to 2.0 g FU and F9 equivalent to 0.5 g FU. The effectiveness of F8 and F9 as attractants and feed stimulants were investigated further in a comparative study against fresh Ulva (FU), dry Ulva (DU) and crude Ulva extract (CE) on T. gratilla (n = 80). Data collected indicated that the treatment with FU was the most effective at both attracting and stimulating T. gratilla compared to the Ulva fractions. The predicted probability of occurrence for attracting T. gratilla was FU > F8 > CE ≥ F9 > DU, while the predicted probability for stimulating T. gratilla to graze was FU > DU > CE > F8 > F9. To assess the effect of nutrient variation on the lipid and fatty acid composition of aquacultured Ulva, the seaweed was cultured for 10 days at six different nutrient concentrations: 0 (control), 25, 50, 75, 100 and 200% NE (NE: nutrient enrichment above ambient seawater concentration; 100% NE = 8.05 nitrogen (N), 3.78 phosphorus (P) and 1.08 potassium (K) g.kg-1 Ulva). Findings showed that nutrient variation did not significantly affect the specific growth rate (SGR) and lipid extracts of Ulva (solvent extraction; chloroform - methanol - phosphate buffer; 1:2:0.8). Lipid classes, obtained by the fractionation of the lipid extracts, were mainly characterized by glycolipids (GL) followed by neutral lipids (NL) and phospholipids (PL). Seaweed grown at low nutrient concentrations (0 and 25% NE; p< 0.05) had significantly lower neutral lipid (NL) contents than Ulva grown at higher nutrient concentrations, while glycolipid (GL) contents were significantly lower in Ulva cultured at a high nutrient concentration (200% NE; p< 0.05). Nutrient variation had no effect on the phospholipid (PL) contents of aquacultured Ulva. Analysis of the fatty acid methyl esters (FAMEs) of the crude Ulva lipid extracts, obtained from culture experiment, by gas chromatography coupled with mass spectrometry (GC-MS) revealed a total of 25 fatty acids (FA). The fatty acid profiled of aquacultured Ulva consisted primarily of saturated fatty acids (SFA) followed by polyunsaturated fatty acids (PUFA) and monounsaturated fatty acids (MUFA). Nutrient variation had no significant effect on the fatty acid content except for the level of C18:0 FA (stearic acid), which was at its lowest value at the highest nutrient concentration (200% NE; p< 0.05). SFA content of Ulva consisted mainly of C16:0 FA (palmitic acid), PUFA of C16:4ω3 (hexadecatetraenoic acid) and MUFA of C18:1ω9 FA (oleic acid). The PUFA content of aquacultured Ulva was comprised mostly of omega-3 FAs (ω-3) compared to ω-6 FAs, with the ω-6:ω-3 ratios ranging between 0.08 to 0.12. Aquacultured U. lacinulata produces a mixture of volatile organic compounds (VOCs) ranging from simple to complex volatile compounds that can contribute to its typical aroma. Tentative identification of VOCs from the solvent extract (dichloromethane - methanol; 2:1), essential oil and head space of aquacultured Ulva analysed by GC-MS, revealed a total of 63 compounds. VOCs from this alga were classed as aldehydes (18), hydrocarbons (15), ketones (10), esters (9), free fatty acids (6), alcohols (4) and aromatic compound (1). Based on the relative content (%) and information available from the literature, only the aldehydes, hydrocarbons, ketones, esters and alcohol are considered as the most important classes of compounds associated with the aroma of this seaweed. Findings also showed that aquacultured Ulva produces VOCs such as benzaldehyde and 6-methyl-5-hepten-2-one that have been shown to be flavour enhancers for high value species including sea urchin. The research from this thesis clearly shows that local aquacultured U. lacinulata is an effective chemoattractant and feed stimulant for the sea urchin T. gratilla. Although the effects of Ulva in its fractionated form (i.e. Ulva fractions F8 and F9) towards T. gratilla was shown to be dose-dependent and less effective than fresh Ulva, findings from this research provide valuable information that may be used in the formulation or supplementation of compound diets to promote consumption, which could be beneficial for the aquaculture industry. This research also provided an improved understanding of the variability of lipid, lipid classes and the FA profile of aquacultured Ulva. Even though a high SFA content was observed, this seaweed has a beneficial PUFA profile with a low ω-6:ω-3 ratio that makes it suitable for human consumption and aquafeed production. Lastly, findings from this study showed that this seaweed produces a mixture of VOCs ranging from simple to complex compounds that may contribute to its typical aroma and the presence of compounds that may be used as flavour enhancers. With the growing interest looking at the commercial application of Ulva around the world, outcomes from this thesis may be of particular interest to the aquaculture, animal feed and human food industries.